“It's hard to talk to a computer, I get it”: An exploratory analysis of clinician connection-building communication practices in rural telepalliative care encounters - Elise C. Tarbi; Natalie Ambrose; Eric C. Anderson; Rebecca N. Hutchinson; Paul K.J. Han; Maija Reblin; Robert Gramling (PEC Innovation)
Context/Objectives: Establishing human connection is critical during serious illness conversations, however the sensory and relational environment of telehealth may require innovative communication practices for clinicians, patients, and families to do so effectively. We sought to explore if and how recommended in-person best practices for establishing human connection are adapted to the telehealth palliative care (telePC) setting, to enable discovery and description of practice innovations in this new care environment. Methods: We analyzed data from the Northern New England Palliative Care TeleConsult Research Study – a formative mixed-methods pilot study at two academic medical centers in rural US states with patients with serious illness (2019–2020). We used a qualitative descriptive approach paired with directed content analysis to analyze video-recorded telePC consultations. Results: Nine video-recorded telePC consultations were analyzed including 9 patients and 6 palliative care clinicians. Patient-participants had a mean age of 68 years, 56 % were women, and 38 % did not complete high school. Mean consultation duration was 52 min (standard deviation 10, range 40–70 min). Our qualitative analysis of visits resulted in three key themes describing clinician communication: 1) Practices for fostering human connection; 2) Practices for overcoming technical problems/difficulties; and 3) Practices for engaging in multi-participant tele-conversations. Conclusion: Our study findings help to provide proof-of-concept evidence that clinicians can use recommended in-person connection-building communication practices in telePC. As palliative care clinicians naturally adapt to telehealth environments, more empirical research is needed to understand which innovative approaches most effectively foster human connection. Innovation: TelePC represents an expanding, yet understudied, mode of palliative care delivery. This study is among the first to describe how the telePC context is catalyzing naturally-occurring communication innovations.